2020
DOI: 10.1002/dev.21955
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' distress exposure and children's withdrawn behavior – A moderating role for the Interferon Gamma gene (IFNG)

Abstract: The dysregulation of the inflammatory response, including pro‐inflammatory molecules, produces neuropsychiatric symptoms and depression‐like behavior, including withdrawal from the physical and social environment. Genetic variants that enhance immune reactivity may thus increase inflammatory and withdrawn reactions to stress. Here we investigated a functional polymorphism of Interferon Gamma gene (IFNG +874 T > A, rs2430561) as moderator of the relationship between mothers’ distress exposure and children's wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Our study supports previous work implicating IFNγ in the stress response and behavior ( Litteljohn et al, 2010 ). Correlations between stress, depression, and IFNγ have previously been shown in the clinic, but the causative relationship and mechanism have not been established ( Mohr and Genain, 2004 ; Pinto et al, 2020 ). Recent studies have also shown that meningeal sources of IFNγ can act directly on neuronal IFNγ receptors to promote the normal development of social behavior ( Filiano et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study supports previous work implicating IFNγ in the stress response and behavior ( Litteljohn et al, 2010 ). Correlations between stress, depression, and IFNγ have previously been shown in the clinic, but the causative relationship and mechanism have not been established ( Mohr and Genain, 2004 ; Pinto et al, 2020 ). Recent studies have also shown that meningeal sources of IFNγ can act directly on neuronal IFNγ receptors to promote the normal development of social behavior ( Filiano et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by studies indicating that mice subjected to direct stress exhibit reduced levels of gut Lactobacillus. Among metabolites involved, it seems that the IFNγ, an inducer of tryptophan conversion to kynurenine produced in response to Lactobacillus, can be sufficient to provide resilience in response to environmental stressors [53,54]. Furthermore, the largest contributor among metabolites that the gut microbiota uses to signal the human brain is tryptophan and its precursors [55].…”
Section: Discussionmentioning
confidence: 99%
“…Correlations between stress, depression, and IFNγ have previously been shown in the clinic, but the causative relationship and mechanism have not been established [54,55]. Recent studies have also shown that meningeal sources of IFNγ can act directly on neuronal IFNγ receptors to promote the normal development of social behavior [42].…”
Section: Discussionmentioning
confidence: 99%